Pan-cancer analysis of chromothripsis-related gene expression patterns indicates an association with tumor immune and therapeutic agent responses - Zhang, Qin; Yang, Lujie; Xiao, He; Dang, Zhaoqian; Kuang, Xunjie; Xiong, Yanli; Zhu, Jianwu; Huang, Zhou; Li, Mengxia (Frontiers in Oncology, 2023)
Chromothripsis is a catastrophic event involving numerous chromosomal rearrangements in confined genomic regions of one or a few chromosomes, causing complex effects on cells via the extensive structural variation. The development of whole-genome sequencing (WGS) has promoted great progress in exploring the mechanism and effect of chromothripsis. However, the gene expression characteristics of tumors undergone chromothripsis have not been well characterized. In this study, we found that the transcriptional profile of five tumor types experiencing chromothripsis is associated with an immune evasion phenotype. A gene set variation analysis (GSVA) was used to develop a CHP score, which is based on differentially expressed gene sets in the TCGA database, revealing that chromothripsis status in multiple cancers is consistent with an abnormal tumor immune microenvironment and immune cell cytotoxicity. Evaluation using four immunotherapy datasets uncovered the ability of the CHP score to predict immunotherapy response in diverse tumor types. In addition, the CHP score was found to be related to resistance against a variety of anti-tumor drugs, including anti-angiogenesis inhibitors and platinum genotoxins, while EGFR pathway inhibitors were found to possibly be sensitizers for high CHP score tumors. Univariate COX regression analysis indicated that the CHP score can be prognostic for several types of tumors. Our study has defined gene expression characteristics of tumors with chromothripsis, supporting the controversial link between chromothripsis and tumor immunity. We also describe the potential value of the CHP score in predicting the efficacy of immunotherapy and other treatments, elevating chromothripsis as a tool in clinical practice.